Analisis Model Prediksi Kebangkrutan Altman Z-Score. Springate dan Zmijewski untuk Menilai Kelangsungan Usaha PT Enseval Putera Megatrading Tbk - Choirunnisa Nurahayu; Evi Yuniarti; Nurmala Nurmala (Jurnal Ilmiah ESAI, 2018)
The economic development of PT EPM Tbk in 2011 to 2016 did not improved, because in 2011 to 2016 the cash flow statement of PT EPM Tbk. decreased. This writing aims to determine the prediction of bankruptcy at PT EPM Tbk with the Altman Z-Score, Springate and Zmijewski Score models to assess the business continuity of PT EPM Tbk from 2011 to 2016. The analysis technique used is the Altman Z-Score bankruptcy prediction model, Springate and the Zmijewski Score for various types of companies. Based on the results of the analysis of the three bankruptcy prediction models Altman Z-Score, Springate Score and Zmijewski Score shows that the business continuity assessment of PT Enseval Putera Megatrading Tbk in 2011 to 2016 is a company in good financial condition or a healthy company and is not at risk The Z-Score is more than the Altman Z-Score, Springate Score and Zmijewski Score standards.Keywords: Altman Z-Score, Springate Score, Zmijewski Score and Business Continuity